The W/S Test for Data Having Neutrosophic Numbers: An Application to USA Village Population. (11th May 2020) - Albassam, Mohammed; Khan, Nasrullah; Aslam, Muhammad
Abstract : The W/S test under neutrosophic statistics is proposed in this paper. The Monte Carlo simulation under the neutrosophic statistical interval method is proposed and applied to study the sensitivity of various neutrosophic statistical distributions. The power of test curves for neutrosophic distributions is presented. The efficiency of the proposed W/S test under neutrosophic statistics is compared with that of the W/S test under classical statistics. The proposed test is explained with the aid of an example.